1917 Or. Gen. and Spec. Laws 805, ch. 377, § 5 - (:unkn) unknown (My University, 1917)
Provided that any person in the business of selling pistols of a size that can be concealed upon his person must obtain a register with the state. This register shall include the date of sale, name of maker, number, caliber, name of purchaser, permanent residence, temporary residence, age, occupation, height, color of skin, color of eyes, color of hair, and signature of purchaser. Failure to keep a register shall be punishable as a misdemeanor
Keywords: CARRY - CONCEALED; REGISTRATION